Strategi Diversifikasi untuk Meningkatkan Pendapatan Komoditi Tomat Beef dan Selada Kering di PT. Momenta Agrikultura Amazing Farm Lembang Jawa Barat - Yumarsono Muhyi; Siti Diana Fathia (Agroinovasi: Jurnal Ilmu dan Teknologi Pertanian, 2024)
Indonesia is an agricultural country where most of its population depends on working in agriculture, especially in the food sector. One of the agricultural sectors that is currently in demand is the cultivation of horticultural crops, this is because the consumption of horticulture such as vegetables and fruits is mandatory to complete the nutritional needs of the human body so that along with the increasing public awareness of nutrition, it also contributes to the increase in demand for raw or processed vegetable products. Tomatoes and lettuce are one type of horticulture that has an important role in improving community nutrition. The content of lime for the formation of bones and teeth and the Fe contained is good for the formation of hemoglobin in the blood. The purpose of this study was to analyze the strategy of PT Momenta Agrikultura to increase income, and analyze the profit of beef tomato and dry lettuce commodities, as well as the financial feasibility of the business in the tomato and lettuce diversification strategy. The method was carried out by collecting field study data and financial feasibility analysis. The results of this study are a strategy analysis carried out by the company with tomato and lettuce diversification to optimize land use, while the results of the feasibility test obtained that the effort to increase income through the tomato and dry lettuce diversification strategy.